PENERAPAN ADMINISTRASI PENGAJARAN PADA KINERJA GURU DI SMP NEGERI 6 SATU ATAP SANDAI - Efendi, Iswan; Asrori, M.; Radiana, Usman (Universitas Tanjungpura, 2026)
This research aims to describe the Application of teaching administration on performance at SMP Negeri 6 Satu Roof Sandai. The form of research used is qualitative research with a case study approach. The participants in this study consisted of 7 individuals, including one male aged 35 years and 6 females aged between 32 - 36 years. All subjects are Educator Management. Data collection methods use observation, interviews and documentation. The data analysis process implements the Miles and Huberman model, namely data analysis is carried out sequentially starting from data reduction, data exposure, and verification or conclusions. The data validity checking technique uses triangulation. The main findings in this research show that: (1) the implementation of teacher teaching administration shows that good administrative management can increase learning effectiveness. 2) Teachers who plan, organize, implement and evaluate teaching in a structured manner tend to have better performance. The implication is that the school, through the implementation of Teacher Administration Management at SMP Negeri 6 Satu Atap Sandai, influences employee performance, particularly in fostering an innovative generation. It emphasizes the importance of internal communication in the implementation of educational administration. Keywords: Administration, Teacher performance, Educator.